PP55 Major behavioural risk factors and mental wellbeing in the general population: a cross sectional analysis of the Health Survey for England. (2nd September 2014) - Stranges, S; Samaraweera, PC; Taggart, FM; Stewart-Brown, S
Abstract : Background: Major behavioural risk factors such as smoking, alcohol consumption, lack of fruit and vegetable intake, and excess body weight are known to adversely affect health outcomes and overall quality of life. However little is known about their impact on positive measures of mental well-being in the general population. The Health Survey for England collected data on mental wellbeing by using the Warwick-Edinburgh Mental Wellbeing Scale (WEMWBS), as well as information on major lifestyle factors in a large representative sample of the English population. Methods: Participants were 13, 983 British adults, aged 16 years and older (56.0% females), with valid responses for the combined 2010 and 2011 datasets. Using multivariate logistic regression analyses, the independent odds ratios (ORs) of low and high mental wellbeing (measured with WEMWBS), as compared to the middle-range category, were estimated for a number of lifestyle variables including body mass index (BMI), smoking and drinking habits, and fruit and vegetable intake. Results: With regard to low mental wellbeing, odds ratios were increased in obese individuals (1.24: 95% CI 1.06–1.45, BMI: 30–40kg/m 2 ; 1.75: 95% CI 1.28–2.39, BMI: 40+ kg/m 2 ); in a linear fashion with increasing smoking (1.77: 95% CI 1.37–2.29, heavy smokers >20 cigarettes/day); and with reduced fruit and vegetable intake (1.55: 95% CI 1.25–1.91, <1 portion/day); whereas odds ratios were reduced for sensible alcohol intake (0.79: 95% CI 0.63–0.93, ≤4 units/day in men, ≤3 units/day in women). As to high mental wellbeing, there were no significant associations with BMI categories or alcohol intake. However, lower odds ratios were found among heavy smokers (0.67: 95% CI 0.47–0.95) and ex-smokers (0.79: 95% CI 0.69–0.90), as well as with reduced intakes of fruit and vegetable (0.77: 95% CI 0.67–0.89, 1 to <3 portions/day). Results were generally consistent across both female and male participants. Conclusion: These novel findings highlight the potential role of major behavioural risk factors as determinants of mental wellbeing in the general population.